Engineering of reinforced shotcrete to support brittle rocks in underground excavations - Toledo Garay, Fernando Enrique (2016)
The most economical and safest support in tunnels and mining work applied up to now in Peru, was the one put into practice in the Cobriza Mine, called Sot-Fer (name given by the miners: due to the metallic confusion of steel by iron) and until now not disseminated in Peru, for unknown reasons. This method of applying reinforced concrete in tunnels and mining works, through the Gunitado or Shotcrete, is the product of the research work, in the Cobriza mine started with the determination of the workloads of the weak rocks constituting the gables of the great mantle of sulfides of 25m of power with Cu, Ag and Bi values. These rocks, which are slates, were studied crystallographically, reaching the conclusion that they crystallize in the Hexagonal system, Rhombohedral division, Hexagonal Scalenodermic class, positive Rhombohedron form {h0hl}. When the ternary axis of the rhombohedron coincides with the vertical axis of the tunnel or the ramp, collapse is generated, losing the full support of the base; if this case does not happen, the rock is self-supporting and does not require support, with this evidence and the specific gravity of the shale the work loads of the support structures were calculated. Supported in ACI 318-81 and in the analysis of arched structures, presented in the books of Timoshenko (Volume II, pp: 97-109) and Olivera López (pp: 127-139); the workloads having been calculated under the proposals of Stagg (pp: 103-124 and 193-222) and Hock (pp: 183-201). Construction steel reinforced shotcrete for underground engineering application is totally different from NMA (New Austrian Method) successfully applied in many countries of the world. This method of applying reinforced concrete using shotcrete is much more efficient, lower cost and more versatile than NMA to adapt to eventual changes in rock stability that occur in mining operations; precisely in the immersion of the steel within the concrete mass.